Pengaruh Herbisida Paraquat Diklorida Oral Terhadap Hati Tikus Putih - Muhartono Muhartono; Yolanda Fratiwi; Indri Windarti; Susianti Susianti (Fakultas Kedokteran Universitas Riau, 2015)
The use of herbicide paraquat dichloride by farmers, is one of effort to increase the production in agricultural sector.Herbicide paraquat dichloride often used by farmers carelessly and there was caution ignorance. Herbicide causemuch adverse effect to organs, especially in liver through oral. The purpose of this study is to determine the effect oforal herbicide paraquat dichloride to hepatocyte swelling and sinusoidal congestion in liver of male rats (Rattusnovergicus) Sprague dawley strain. In this experimental study, 25 male rats (Rattus novergicus) Sprague dawleystrain are divided randomly into 5 group and treated for 2 days. K1 is group of controlled, K2, K3, K4, K5 are givenherbicide paraquat dichloride 25 mg/kgBW, 50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW. The results showedthat the average number of hepatocyte swelling and sinusoidal congestion in liver was increasing. In Kruskal Wallistest and Post Hoc Mann Whitney test found significant difference p=0.000 (p<0.005). There are significant effect oforal paraquat dichloride to hepatocyte swelling and sinusoidal congestion in liver of male rats (Rattus novergicus)Sprague dawley strain.